Digital Financial Twins in Islamic Microfinance: Evidence from Conflict-Affected Rural Economies (2020–2025) - Sharifi, Ahmad Khosrow; Yar, Fayaz Gul Mazloum (Randwick International of Social Science Journal, 2025)
Conflict affected rural microfinance faces data scarcity and repayment volatility, limiting sustainable outreach. No prior empirical study has evaluated Digital Financial Twin (DFT) analytics within Shariah compliant institutions under conflict conditions. We integrate cyber physical simulation with Islamic microfinance, offering the first large scale evidence of DFT impact on financial and poverty outcomes. We employ a quasi experimental design combining geospatial conflict data (ACLED), loan level records from five Islamic MFIs (N = 48,360 loans across 120 rural districts), and UNDP Multidimensional Poverty Index scores. Multivariate logistic regressions, structural equation modeling (SEM), and GIS mapping were implemented using R (v4.2.2) and lavaan (v0.6 12). DFT deployment correlates with a 5.8 pp increase in on time repayment (OR = 1.27, 95% CI [1.18, 1.37], p < 0.001) and a 5.9 pp reduction in default rates (OR = 0.72, 95% CI [0.64, 0.81], p < 0.001). SEM indicates a significant moderating effect of DFT on conflict intensity (β = 0.29, p < 0.01). GIS heatmaps demonstrate sustained outreach in high conflict zones. DFT analytics enhance Shariah compliant microfinance performance and resilience in fragile settings, informing policy on digital infrastructure investment in conflict affected economies.